Management of cerebrospinal fluid leak from cervical gunshot wounds with external ventricular drainage: a small case series. Issue 12 (7th December 2020) - Crutcher, Clifford L; Wilson, John M; Morrow, Kevin D; Shields, Jessica A; Lasseigne, Lindsay M; Culicchia, Frank; Tender, Gabriel
Abstract: Historically, the surgical management of gunshot wounds to the spine has been controversial. Repair of a persistent cerebrospinal fluid (CSF) leak is a generally agreed upon indication. The management of such CSF leaks typically involves lumbar drainage or direct surgical repair. Here, the authors report two cases of CSF diversion with an external ventricular drain (EVD) in patients with cervical gunshot wounds. Both patients had spinal canal obliteration or physiologic myelographic block at or below the level of injury. To the best of the author's knowledge, these are the first two reports of successful EVD treatment of persistent CSF leaks related cervical gunshot wounds. The authors also propose a CSF treatment algorithm for cervical gunshot wounds that includes EVD.